Phenotypic plasticity of the stem epidermis in the bluegrasses (Poa L.) of section Stenopoa Dumort. (Poaceae). II. Xeromorphic species - Olonova, Marina V.; Shiposha, Valeria D.; Romanets, Roman S.; Singh, Harsh (Acta biologica sibirica)
Section Stenopoa is one of the most significant among the bluegrasses, and its proper identifying is important task. The epidermal characters, which determine the degree of roughness of the bluegrasses, are used widely in botanical literature, but the information on bluegrasses characters is controversial frequently. This work is devoted to the study of xeromorphic representatives of the section. The aim of this work was to assess the variability of the sculptural features of the epidermis, which determine the degree of roughness of the stems within xeromorphic bluegrass of the Stenopoa section, and the possibility of using these characters in taxonomy. The types of epidermal trychomes and their variability and frequencies within the populations of 12 species were researched using SEM and light microscope. As a result of the study, no species-specific types of epidermal structure were revealed. In all the studied species, with the exception of the Central Asian hybridogenic species Poa psilolepis, the epidermis of the stem and leaf sheaths contained crown cells and pricles or bristles in varying proportions. Under the panicle only crown cells or pricles directed upwards were observed. The most species showed high interpopulation and intrapopulation variability. At the same time, the Central Asian species were distinguished by less polymorphism and a small number of deviated individuals in the populations. The conducted studies cast doubt on the possibility of widespread use of epidermal sculpture as a discriminator for xeromorphic Stenopoa species, including for distinguishing between the Siberian P. stepposa and the European P. erythropoda.